2011
DOI: 10.1177/0309364611406169
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction following lower-limb amputation

Abstract: Background: Patient satisfaction is an important measurement in healthcare for administrators, clinicians and patients. Objectives: This study investigated the role of gait deviation in patient satisfaction following lower-limb amputation and prosthesis prescription. Study design: A cross-sectional study was done. Methods: Twenty community-based unilateral lower-limb amputees, 12 transtibial and 8 transfemoral, were recruited from support groups. Participants completed the prosthesis evaluation questionnaire (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
59
3
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(76 citation statements)
references
References 31 publications
(43 reference statements)
3
59
3
5
Order By: Relevance
“…Use of a prosthesis may promote independence in activities that incorporate the lower limb (e.g., postural transitions, locomotion), but prominent deficits remain. Standing balance [12], level-ground walking [13][14][15][16][17][18], stair ascent and descent [19][20][21], hill ascent and descent [22], negotiation of uneven terrain [14], standing from and sitting in a chair [23], and obstacle avoidance [24] have been reported to be significantly impaired in persons with TFA compared to nondisabled control subjects. Documented limitations typically relate to the capacity of prosthetic users to engage in specified activities compared with those without amputation in controlled laboratory environments.…”
Section: Introductionmentioning
confidence: 99%
“…Use of a prosthesis may promote independence in activities that incorporate the lower limb (e.g., postural transitions, locomotion), but prominent deficits remain. Standing balance [12], level-ground walking [13][14][15][16][17][18], stair ascent and descent [19][20][21], hill ascent and descent [22], negotiation of uneven terrain [14], standing from and sitting in a chair [23], and obstacle avoidance [24] have been reported to be significantly impaired in persons with TFA compared to nondisabled control subjects. Documented limitations typically relate to the capacity of prosthetic users to engage in specified activities compared with those without amputation in controlled laboratory environments.…”
Section: Introductionmentioning
confidence: 99%
“…Patients consistently prefer energystorage-and-return (ESAR) prosthetic feet [6][7][8], but the typical biomechanical metrics used to assess gait do not always demonstrate superiority of ESAR. Furthermore, Kark and Simmons showed a lack of relationship between gait deviations and prosthesis satisfaction, implying the role of gait is not unambiguously coupled to prosthesis satisfaction [9]. Numerous biomechanics measures covering all areas of kinematics and kinetics as well as electromyography and energy expenditure have been explored in gait of individuals with lower-limb amputation [6].…”
Section: Introductionmentioning
confidence: 99%
“…While this technique is informative, it fails to account for the inherent relationship between strides that calculations such as the largest Lyapunov exponent (LyE) will capture. Measures, such as those utilized by Kark and Simmons [9], presume that every step is completely independent of the previous steps and has no influence on any ensuing steps. However, studies have confirmed the presence of strong relationships between continuous strides during gait [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Dillingham et al [7] conducted a survey and noticed that most of the participants ( n = 146) were not satisfied with their prostheses due to skin problems and pain. Another study [29] also revealed dissatisfaction with prostheses. Moreover, more than 70% of participants in a study were more satisfied with the pin/lock suspension system than the Pelite liner [30].…”
Section: Introductionmentioning
confidence: 99%